2004
DOI: 10.1213/01.ane.0000099722.80132.17
|View full text |Cite
|
Sign up to set email alerts
|

Massive Rupture of a Hepatic Hydatid Cyst Associated with Mechanical Ventilation

Abstract: We present a case of massive rupture of hepatic Echinococcus cyst associated with mechanical ventilation. We believe that the use of a double-lumen endotracheal tube could be crucial in the management of the hydatid cysts of the liver with thoracic involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Another common site of Echinococcus cysts localization includes the lungs (5 % to 16 %) and the liver together with the lungs can be affected simultaneously in about 5 -13 % of cases. However, cysts may also affect other locations, including the brain, the spleen, soft tissues, bones and the spinal extra-dural space (Gόmez et al, 1995;Anthi et al, 2004;Kir et al, 1995). In our study, simultaneous occurrence in the liver and lungs was confirmed in 3 (10 %) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another common site of Echinococcus cysts localization includes the lungs (5 % to 16 %) and the liver together with the lungs can be affected simultaneously in about 5 -13 % of cases. However, cysts may also affect other locations, including the brain, the spleen, soft tissues, bones and the spinal extra-dural space (Gόmez et al, 1995;Anthi et al, 2004;Kir et al, 1995). In our study, simultaneous occurrence in the liver and lungs was confirmed in 3 (10 %) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous rupture of an echinococcal cyst is not infrequent in the liver but occurs only rarely in the lung. [1][2][3] To our knowledge, this is the first case report of spontaneous hydatid cyst rupture into the bronchial tree with anaphylactic shock and acute respiratory distress syndrome. Learning point N Spontaneous rupture of an echinococcal cyst in the lung is a rare clinical entity and may cause anaphylactic shock and acute respiratory distress syndrome.…”
mentioning
confidence: 99%
“…[8,9] The magnitude of allergic reactions ranges from mild hypersensitivity to fatal anaphylactic shock. [10,11] Pheochromocytoma secretes predominantly norepinephrine. Sustained severe hypertension is often the most common presentation of pheochromocytoma.…”
Section: Discussionmentioning
confidence: 99%